When does earnings management matter? Evidence across the corporate life cycle for non-financial Chinese listed companies - Ammar Hussain; Minhas Akbar; Muhammad Kaleem Khan; Ahsan Akbar; Mirela Panait; Marian Cătălin Voica (Journal of Risk and Financial Management, 2020)
Information availability, firm performance, idiosyncratic volatility and bankruptcy-risk vary across the Corporate Life Cycle (CLC) stages. The purpose of this paper is to examine whether CLC stages explain firm's propensity to engage in both accrual base and real earning management practices in the context of China. Panel data of 3250 non-financial Chinese listed firms spanning from 2009 to 2018 is used to investigate the proposed relationship. CLC stages were captured through Dickinson's model, while earnings management is measured by employing both techniques, i.e., accruals-base earnings management and real earnings management. The data were analyzed through Panel data fixed-effects and random-effects techniques. Results reveal that, when compared to shakeout phase, managers' response to use both earnings management practices is significantly higher during introduction and decline phases, and lower during growth and mature stages of CLC. It suggests that introductory and later-staged firms distort their factual financial information from creditors to obtain loans without strict debt covenants. Our results are robust to alternate measures and specifications. The core contribution of this research is to add a fresh perspective to the CLC research by uncovering its imperative role in influencing the earning management behavior of corporate managers.
Keywords: 330; corporate life cycle; earnings management; accruals-base earnings management; real earnings management; China; debt covenants